(untitled) (AYUSHDHARA, 2025)
The traditional description of the hand’s superficial palmar arch highlights its formation through an anastomosis between the ulnar artery and the superficial palmar branch of the radial artery. However, the actual structure of the arch show significant variation, both in the size of the contributing arteries and due to the presence of additional branches from other arteries that may also contribute to its formation. Material and Results: A case of unilateral presence of incomplete superficial palmar arch has been found with respect to its course and branching. This variation was found on the left-hand palmar aspect of a 72-year-old male cadaver during regular anatomical dissection. Non arch codominant subtype ulnar/radiopalmar pattern of superficial palmar arch was found with varied branching pattern. Conclusions: The anatomical knowledge of the variability in the arch formation becomes important in the application of surgical techniques that can help treating pathologies of the hand.